Studi Keragaman Pteridophyta Terestrial Di Kawasan Hutan Sekipan Desa Kalisoro Tawangmangu Karanganyar Provinsi Jawa Tengah - Viyanti, Beta Okta, Efri Roziaty, S. Si., M. Si sel (2017)
The research on the diversity of terrestrial pteridophytes in Sekipan area of Kalisoro Village Tawangmangu Karanganyar Central Java Province, was conducted on April 2017. The purpose of this research was determening the level of diversity terrestrial pteridophytes in Sekipan forest area. The location of the study was determined by purposive sampling consisted of 10 plots. Results of the study found 12 species divided into 4 families consisted of Thelypteridaceae (Thelypteris resinifera), Dennstaedtiaceae (Microlepia strigosa), Cyatheaceae (Cyathea contaminans), and Polypodiaceae consisting of Diplazium velutinum, Adiantum hispidulum, Pteris biurita, Deparia petersenii, Nephrolepis Exaltata, Chingia ferox, Nephrolepis sp., Pityrogramma calomelanos, and Davallia denticulata. The dominant percentage can be seen from calculation highest INP results is Diplazium velutinum, while the lowest INP value there are two types of Chingia ferox and Cyathea contaminans. Known on the result index of diversity (H ') is 0.864. It can be said that the diversity of pteridophytes in Sekipan forest area belongs to a low category.